1998
DOI: 10.1029/98jd01279
|View full text |Cite
|
Sign up to set email alerts
|

Observations of isoprene chemistry and its role in ozone production at a semirural site during the 1995 Southern Oxidants Study

Abstract: Abstract. Isoprene and its oxidation products, methyl vinyl ketone (MVK) and mcthacrolein (MACR), were measured in a semirural environment that was occasionally heavily impacted by urban emissions. At this site, isoprenc was the most important hydrocarbon in terms of koH' [hydrocarbon], but the aldehydes HCHO and CH3CHO also appear to be very important. The local isoprene photochemistry appears to be occasionally enhanced in NOx-rich urban plumes that are advected to the site over intermediate forested land. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…The movement of O 3 precursors to suburban areas leads to a high concentration of O 3 in these areas. Several previous studies e.g., by Trainer et al (1987), Chameides et al (1992), Roberts et al (1998), Starn et al (1998) and Wiedinmyer et al (2001) have indicated that the amount of biogenic VOC, such as isoprene, can contribute to the quantity of surface O 3 . Nevertheless a study by Von Schneidemesser et al (2011) indicated that the contribution of biogenic VOCs were quite low compared to the contribution of ozone from anthropogenic precursors such as NO x and VOCs which originated from motor vehicles and industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…The movement of O 3 precursors to suburban areas leads to a high concentration of O 3 in these areas. Several previous studies e.g., by Trainer et al (1987), Chameides et al (1992), Roberts et al (1998), Starn et al (1998) and Wiedinmyer et al (2001) have indicated that the amount of biogenic VOC, such as isoprene, can contribute to the quantity of surface O 3 . Nevertheless a study by Von Schneidemesser et al (2011) indicated that the contribution of biogenic VOCs were quite low compared to the contribution of ozone from anthropogenic precursors such as NO x and VOCs which originated from motor vehicles and industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…Its global emission was estimated to be 500-750 Tg yr À1 (Guenther et al, 2006), which is several times higher than the anthropogenic VOCs emissions (100-200 Tg yr À1 ) (Olivier and Berdowski, 2001), and typically more reactive than anthropogenic VOCs (Abelson, 1988). Researches conducted over the past decades have shown that isoprene contributes significantly to tropospheric ozone formation in rural (Trainer et al, 1987), suburban (Starn et al, 1998), and even urban areas (Chameides et al, 1988;Biesenthal and Shepson, 1997;Lee and Wang, 2006). Recently, ozone formation potentials (OFPs) based on the observed atmospheric VOCs in a typical region were widely utilized to evaluate the reaction activity of the individual species to local atmospheric ozone formation (Wiedinmyer et al, 2001;Duane et al, 2002;Duan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Isoprene emission occurs mostly during the daytime, increasing with temperature and radiation over the course of the morning and falling off in the afternoon (Fehsenfeld et al, 1992). Several studies have found reaction with NO 3 to be the dominant loss process for isoprene that remains during the early evening in moderately 4946 A. E. Perring et al: A product study of the isoprene+NO 3 reaction polluted environments (∼15% of the total) (Stroud et al, 2002;Warneke et al, 2004), and that this can result in substantial conversion of NO x to organic nitrates at night (Starn et al, 1998). Not only is NO 3 an important isoprene sink but, because of the high yield, INs formed by NO 3 -initiated oxidation may represent a large fraction of the total IN source (Horowitz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%